Korelasi Durasi Penggunaan Smartphone dengan Kualitas Tidur dan Prestasi Belajar Siswa - Anggreny, Yecy; Sari, Siska Mayang; Anisa, Nurlaila (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the correlation of the duration of smartphone use with sleep quality and learning achievement of Riau Banking Vocational School students. The method used is a correlation design with a cross sectional approach. The results showed that there was a relationship between the duration of smartphone use with sleep quality with a p-value of 0.002. As for the duration of smartphone use with learning achievement, there is no relationship with a p-value of 0.156. It is concluded that the duration of smartphone use is one of the factors that affect sleep quality in adolescents and for learning achievement there are other factors that affect student achievement. Keywords: Duration of smartphone use, sleep quality, learning achievement, and adolescents.